Pengaruh Celebrity Endorsement Terhadap Keputusan Pembelian British Propolis - Elakarci, Rizky Ramadevi; Nurlenawati, Netti; Triadinda, Dexi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Celebrity endorsement is a marketing strategy that, when designed effectively, can have a significant impact on consumer behaviour and purchasing decisions. The following study explains the role of visibility, credibility, attractiveness, and celebrity power in influencing purchasing decisions for British Propolis products. A quantitative approach was chosen as the research method, with data obtained from 155 respondents who answered an online questionnaire. The data was analysed using multiple linear regression analysis with the assistance of SPSS software version 24. The regression analysis results indicate that credibility, attractiveness, and power have a significant impact on purchasing decisions, while visibility does not. The findings of this study provide insights into the effectiveness of celebrity endorsements in increasing sales transactions and offer recommendations for future marketing strategies. Celebrity endorsement is a marketing strategy that, when designed effectively, can have a significant impact on consumer behaviour and purchasing decisions. The following study explains the role of visibility, credibility, attractiveness, and celebrity power in influencing purchasing decisions for British Propolis products. A quantitative approach was chosen as the research method, with data obtained from 155 respondents who answered an online questionnaire. The data was analysed using multiple linear regression analysis with the assistance of SPSS software version 24. The regression analysis results indicate that credibility, attractiveness, and power have a significant impact on purchasing decisions, while visibility does not. The findings of this study provide insights into the effectiveness of celebrity endorsements in increasing sales transactions and offer recommendations for future marketing strategies.